1999
DOI: 10.1074/jbc.274.18.12316
|View full text |Cite
|
Sign up to set email alerts
|

The Recombinant Azotobacter vinelandii Mannuronan C-5-Epimerase AlgE4 Epimerizes Alginate by a Nonrandom Attack Mechanism

Abstract: The Ca 2؉ -dependent mannuronan C-5-epimerase AlgE4 is a representative of a family of Azotobacter vinelandii enzymes catalyzing the polymer level epimerization of ␤-D-mannuronic acid (M) to ␣-L-guluronic acid (G) in the commercially important polysaccharide alginate. The reaction product of recombinantly produced AlgE4 is predominantly characterized by an alternating sequence distribution of the M and G residues (MG blocks). AlgE4 was purified after intracellular overexpression in Escherichia coli, and the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
91
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 79 publications
(100 citation statements)
references
References 47 publications
9
91
0
Order By: Relevance
“…The 1-13 C-labeled and unlabeled mannuronan (100% M, chemically deacetylated) were prepared from an epimerase-defective (algG) P. fluorescens mutant (18,43). Alginate containing alternating MG residues (MG-alginate) was produced in vitro from mannuronan by using recombinantly produced AlgE4 (23). Alginate from the leaves of Laminaria hyperborea and LF 10/60, which is an L. hyperborea stripe alginate, were obtained from FMC Biochemicals, Drammen, Norway.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 1-13 C-labeled and unlabeled mannuronan (100% M, chemically deacetylated) were prepared from an epimerase-defective (algG) P. fluorescens mutant (18,43). Alginate containing alternating MG residues (MG-alginate) was produced in vitro from mannuronan by using recombinantly produced AlgE4 (23). Alginate from the leaves of Laminaria hyperborea and LF 10/60, which is an L. hyperborea stripe alginate, were obtained from FMC Biochemicals, Drammen, Norway.…”
Section: Methodsmentioning
confidence: 99%
“…Because both enzymes are identical in their N-terminal parts and are expressed in the same vector system, these results strongly indicated that the AlgE4 R-module can stimulate the activity of the PsmEA-module, despite the significant differences (61% identity) in the primary sequences of the A-modules of these two enzymes. Coomassie-stained SDS-PAGE gels and Western blots showed that an exact quantification of this stimulation was difficult to obtain due to the production of several forms of these enzymes in E. coli, as previously described for AlgE4 (23). The epimerization pattern generated by PsmEAR was also determined by 1 H NMR spectroscopy, using partially purified enzyme, as described for PsmE and PsmEA.…”
Section: Activity Of Psme On G-containing Alginate Substrates-mentioning
confidence: 99%
See 1 more Smart Citation
“…The NMRbased assay, 23 whose result is shown in Figure 6, certified that A-[ 15 N]-R epimerizes poly-M-alginate to the typical MG-pattern characteristic for AlgE4. 24 As the A-module alone is also active, 30 this is not necessarily a proof for the presence of active AlgE4. However, the epimerisation rate of the A-module alone is significantly lower than that of full-size AlgE4.…”
Section: Activity Studiesmentioning
confidence: 99%
“…Although highly homologous, these enzymes each create characteristic M/G patterns producing alginates with different properties. AlgE4 which is the smallest epimerase containing one A-module and one R-module makes predominantly alternating M/G structure acting on polyM by a processive mode of action [14][15][16] . AlgE1, AlgE2, AlgE3, AlgE5 and AlgE6 make G-blocks of varying lengths, and AlgE6 is the epimerase able to make the longest G-block structures when acting on polyM 17 .…”
Section: Introductionmentioning
confidence: 99%